Perlindungan Hukum UMKM dalam Memasuki Era Baru Pasca Pandemi - Sopamena, Siska Indah Vilonia; Rumahlewang, Fruli; Sahuburua, Alfred Graciano; Sopamena, Ronald Fadly (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2022)
Introduction: This article analyzes MSMEs in general and the legal protection of MSMEs during the pandemic and the protection of MSMEs entering a new era after the pandemic.Purposes of the Research: The purpose of this article is to understand the impact of the pandemic for MSMEs as well as legal protection for MSMEs in entering a new era after the pandemic.Methods of the Research: This study uses a normative juridical method by using a statute approach and also a conceptual approach.Results of the Research:  The results showed that businesses that had to be closed in an effort to stop the spread of the virus were one of the main reasons for the bankruptcy of MSMEs. The absence of production and sales activities certainly has a big impact on MSMEs that do have small capital. The government is obliged to provide legal protection for MSMEs, especially in entering the post-pandemic era. By utilizing technological advances, MSMEs can take advantage of social media and marketplaces so that they can sell their products through internet media. With the challenges that must be faced by MSME actors to market their businesses, the policies that have been made by the government such as tax incentives, credit restructuring, MSME working capital loans, and other support emerged as economic recovery in the MSME sector. However, the effectiveness of this policy is still questionable because the recovery for MSMEs is still running very slowly even though the government has implemented actions to support the community and support MSMEs with various kinds of waivers. For this reason, the government must work optimally to supervise and provide assistance so that MSMEs in Indonesia are ready to enter a new era after the pandemic